Receipt of Palivizumab before Birth Hospitalization Discharge among Preterm Infants in the United States - La Gamma, Edmund F.; Kumar, Veena R.; Wadhawan, Rajan; Ye, Sherry; Sifakis, Frangiscos; Ycas, Joseph; Ambrose, Christopher S. (American Journal of Perinatology, 2015)
Objective This study aims to determine predischarge palivizumab receipt prevalence among infants ≤ 36 weeks' gestational age.Study Design This retrospective cohort study used hospital discharge records from the Premier Perspective database (Premier Inc., Charlotte, NC) of infants ≤ 36 weeks' gestational age who were discharged home after birth hospitalization during the November–March respiratory syncytial virus (RSV) seasons from 2006 to 2011. Descriptive statistics were performed and logistic regression was employed to identify differences in categorical variables.Results Among infants ≤ 36 weeks' gestational age discharged home during the RSV seasons, 21.4 to 27.0% had a record of palivizumab receipt before discharge. Among infants ≤ 30 weeks' gestational age, palivizumab receipt was 82.3 to 88.8%. Receipt varied considerably at the hospital level, from 0 to 100%.Conclusion This study improves our understanding of characteristics associated with predischarge palivizumab administration. The identified gaps in recommended care can help inform future implementation of palivizumab and other interventions to help improve the health of high-risk preterm infants in the United States.
Keywords: palivizumab; preterm infants; respiratory syncytial virus; vitamin K; hepatitis B vaccine